Being Small for Gestational Age does not Change Short-Term Outcomes for Extremely Low Birth Weight Babies at Townsville University Hospital - Williamson, Natalee; Alcock, Gary; Kandasamy, Yoga (Journal of Child Science, 2022)
Aim To determine whether being small for gestational age (SGA) is associated with increased mortality and short-term morbidity for extremely low birth weight (ELBW) babies at Townsville University Hospital (TUH).Methods All babies with a birth weight of <1,000 g born at TUH between January 1, 2010 and January 1, 2021 were included. Data from the neonatal unit's NeoDATA database were used to compare mortality and short-term morbidity outcomes for babies categorized as SGA (birth weight <10th centile) or not. Statistical analyses were used to determine associations between being SGA and survival to discharge, intubation for mechanical ventilation, duration of respiratory support, chronic neonatal lung disease (CNLD), home oxygen, intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL), retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC), sepsis, time to full enteral feeds, and duration of admission.Results Of 461 ELBW babies, 62 (13.4%) were SGA. The SGA babies were significantly smaller at 714 (580–850) versus 810 (700–885) g (p < 0.001) and of advanced gestational age at 28.6 (26.6–30.2) versus 25.4 (24.4–26.6) weeks (p < 0.001). No significant difference in mortality existed, with 85% of SGA babies and 84% of others surviving. On univariate analysis, being SGA was associated with significant reductions in intubation for mechanical ventilation (p < 0.001), duration of respiratory support (p < 0.001), intraventricular hemorrhage (p = 0.002), NEC (p = 0.037), and admission duration (p = 0.038). After controlling for confounding factors, no outcomes were independently associated with being SGA. Logistic regression found survival was associated with birth weight (p = 0.030), gestational age (p = 0.007), and antenatal corticosteroids (p = 0.008).Conclusions Being SGA is not an independent predictor of mortality nor adverse short-term morbidity for ELBW babies.
Keywords: Small for gestational age; growth restricted; extremely low birth weight; premature; mortality; morbidity